Investigating the mechanism of oridonin against triple-negative breast cancer based on network pharmacology and molecular docking - Yuan Zhao; Song Lan; Xinyu Li; Yimin Deng; Limei Sun; Diping Yu (PLoS ONE, 2025)
Oridonin, a tetracyclic diterpenoid from Rabdosia rubescens (Hemsl.) Hara, exhibits various pharmacological actions, such as anti-tumor, anti-infective, and anti-inflammatory properties. However, the underlying pharmacological effects of oridonin on triple-negative breast cancer (TNBC) are yet to be elucidated. This study aims to examine the molecular mechanism and pharmacological impact of oridonin on TNBC using a network pharmacological strategy. Initially, the pharmacological databases and analysis platforms were employed to identify the potential targets of oridonin using the GeneCards website. The process of standardizing gene names involved the conversion of all target genes using the UniProt database. The acquired data was subjected to identify prevalent target genes. Then, these genes were examined using the STRING website to create a protein-protein interaction (PPI) network. In addition to Gene ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, a molecular docking analysis was conducted to validate the binding conformation between oridonin and the putative target genes. Among the selected 549 genes, 106 genes were found to interact with TNBC. The KEGG study suggested that the underlying mechanism could potentially be linked to the PI3K/Akt signaling pathway and proteoglycans in cancer. Moreover, molecular docking studies indicated that oridonin exhibited the strongest binding affinity with AKT1 (binding energy: −11.40 kcal/mol) and significant associations with other major targets, including EGFR, NFKB1, MAPK1, and SRC. In summary, the resultant findings based on molecular docking and network pharmacology could demonstrate the potential applicability of oridonin for treating TNBC through pathways like PI3K/Akt signaling.